2022
DOI: 10.1007/s11109-021-09758-y
|View full text |Cite
|
Sign up to set email alerts
|

Christian Nationalism and Political Violence: Victimhood, Racial Identity, Conspiracy, and Support for the Capitol Attacks

Abstract: What explains popular support for political violence in the contemporary United States, particularly the anti-institutional mob that attacked the U.S. Capitol in January 2021? Recent scholarship gives reason to suspect that a constellation of beliefs known as “Christian nationalism” may be associated with support for such violence. We build on this work, arguing that religious ideologies like Christian nationalism should be associated with support for violence, conditional on several individual characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 49 publications
6
50
3
Order By: Relevance
“…6 An issue that requires discussion is why the associations were generally consistent across racial identity and gender. In contrast with numerous other studies (e.g., Armaly et al 2022;Gorski and Perry 2022;Perry, Cobb, et al 2022;, black and white Americans did not diverge sharply in their patterns of association between Christian nationalism and political attitudes. And only Hispanics showed minor slope differences from whites.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…6 An issue that requires discussion is why the associations were generally consistent across racial identity and gender. In contrast with numerous other studies (e.g., Armaly et al 2022;Gorski and Perry 2022;Perry, Cobb, et al 2022;, black and white Americans did not diverge sharply in their patterns of association between Christian nationalism and political attitudes. And only Hispanics showed minor slope differences from whites.…”
Section: Discussioncontrasting
confidence: 97%
“…A later study found that beyond inclining white Americans to affirm more economic messages in line with "rugged individualist" notions of achievements and failures, white Americans who center civic belonging about "Christian heritage" are simultaneously more likely to acknowledge instances of injustice against Black Americans while also indicating belief in anti-white discrimination being pervasive in American society (Perry, Cobb, et al 2022). Armaly et al (2022) found that white Americans who affirmed Christian nationalism were especially more likely to support violent extremism compared to nonwhites. And most recently, Gorski and Perry (2022) find that while white Americans' views on racial discrimination are significantly influenced by Christian nationalist the same is not true among Black Americans.…”
Section: Expectationsmentioning
confidence: 96%
See 2 more Smart Citations
“…with strong pre-existing social identities such as partisanship (Armaly et al, 2022;van Prooijen et al, 2015) Hence, counter terrorist officials in the European Union and the United States have warned about "new forms of terrorism" motivated by conspiracy theories (Anon, 2019;Pantucci, 2020).…”
Section: Evidencementioning
confidence: 99%